Al-Ghazali and the Crusades: Bennabian perspective - Alatas, Alwi; Suleiman, Hassan (Al Hikmah Research & Publications Centre, 2019)
Jerusalem fell into the hands of the crusaders at the end of the eleventh century. The fall of the city actually reflected the internal problem of Muslim civilisation. It was almost nine decades later that Jerusalem was successfully recaptured by Ṣalāḥ al-Dīn al-Ayyūbī (d. 1193). Some scholars have a view that Ṣalāḥ al-Dīn’s victory was in fact an outcome of Sunni revival triggered by the spiritual thought or taṣawwuf of Abū Ḥāmid al-Ghazālī (d. 1111). This view becomes even more interesting when examined with the theory of civilisation developed by Malik Bennabi (d. 1973), a twentieth century Algerian Muslim thinker. Some scholars have discussed Malik Bennabi’s thought, but it seems few, if any, have used his theory to interpret certain historical chapter. This article attempts to re-read the history of the struggle for Jerusalem in the crusading period through Bennabi's perspective and discusses the importance of al-Ghazālī in this struggle.